Prarancangan Pabrik Etilen Dari Cracking Nafta Menggunakan Proses Maxene Dengan Disain Alat Utama Reaktor Thermal Cracking - Abdul Hafiz Hidayat; Komalasari Komalasari (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Ethylene is one of the most important petrochemical substances and it’s uses as raw material for various products. The last products made with ethylene include food packaging, toys, food containers, bottles, pipes, antifreeze, carpets, insulation, household appliances, etc. Chemicals made from ethylene to produce end products such as polyethylene, ethylene dichloride, ethylene oxide, ethylbenzene, and vinyl acetate. The ethylene production process is carried out by feeding naphtha into the thermal cracking reactor and a production capacity of 155,000 tons / year is obtained. In the thermal cracking reactor design to break the hydrocarbon chain of naphtha, the feed temperature is 650 oC with a feed flow rate of 70,620.95 kg/hour dimensions of the thermal cracking reactor is 20 ft long, 40 ft wide and 100 ft high including chimney 100 ft. Heat (Q) required is 88,314,298.72 Btu / hour. The amount of Fixed Capital Investment (FCI) is 45,879,155.2. The Cost of Working Capital Investment (WCI) is 8,096,321,505 and the Total Capital Investment (TCI) cost is 53,975,476.7. The Cumulative Cash Ratio (CCR) values for nondiscounted and discounted 10% are 2.2 and 1.21, respectively. The amount of rate of return on investment (ROROI) is 22.7%, Pay Out Time (POT) for non-discounted profitability and discounted 10% profitability are 3.46 years and 6.84 years respectively, the value of the Discounted cash flow rate of return (DCFROR) is 13.55% and every 2% increase in sales and investment (FCI) there is a change in NPV of 129,886,499.71. Therefore based on the analysis that has been done it can be concluded that the factory is feasible to build. Keywords: ethylene, naphta, thermal cracking, total capital investment